ASAS PERSONALITAS DALAM KONTRAK DAN IMPLEMENTASINYA PADA KERJASAMA BADAN LAYANAN UMUM RUMAH SAKIT DENGAN BADAN USAHA SWASTA - Winarto, Eko; Tanjung, Afriansyah (Universitas Stikubank, 2026)
ABSTRACT Hospitals can be established by the Central Government, Regional Government, or the Community. Hospital management organized by the Government can apply the financial management pattern of BLU or BLUD. Hospital independence can be achieved through healthy business processes. The dual role of hospitals as public services and business entities. The commercial health sector is increasingly closely linked to the global health industry. Collaboration between BLU hospitals and private business entities is often manifested in KSO contracts. KSO contracts must contain legal principles (rechtbeginselen) which serve as basic norms and guidelines in the formation or creation of legal regulations. The principle of personality in KSO contracts is important to ensure the parties' performance is balanced. This study uses a normative or doctrinal legal research methodology by examining primary legal sources in the form of KSO contracts between BLU hospitals and private business entities, the Civil Code, and other material laws. A study was also conducted on secondary legal sources in the form of legal materials consisting of books or legal journals regarding legal principles, the views of legal doctrines, and the results of legal research. Keywords : Principle of Personality, Public Service Agency, Operational Cooperation Contract.